Trauma Practice in the Wake of September 11, 2001. - Gold, Steven N. (Taylor and Francis, 2014)
Trauma practitioners and educators: are you ready to meet the challenges of the aftermath of terrorist attacks?Trauma Practice in the Wake of September 11, 2001 will show you how frontline trauma practitioners responded to the crisis of the terrorist attacks. In keeping with Haworth's mission to provide practitioners and educators with timely information on the assessment and treatment of trauma, this essential book responds to the traumatic impact of the events of September 11th, 2001 and their implications for trauma practice. In Trauma Practice in the Wake of September 1.